(untitled) (Andamios, Revista de Investigación Social, 2007)
This paper is intended to (1) outline the metamethodological proposal by Larry Laudan in his book Beyond Positivism and Relativism (1996), which would provide a foundation for the evaluation of scientific methodologies, that warrants —according to the authorobjectivity in sciences and (2) develop a detailed criticism of two theses from this proposal. I suggest these theses are not justified so that a reformulation or radical change would be needed in order for the objectivity of science to be maintained. However, replacing a metamethodology with another could be misleading, since this eludes the fundamental skeptical problem of the justification of knowledge. I will not conclude the end of philosophy in skepticism; nevertheless, my arguments point towards this very overwhelming direction.